Further revision of the genus Megalopsalis (Opiliones, Neopilionidae), with the description of seven new species - Taylor, Christopher (Pensoft Publishers, 2013)
The Australian harvestmen genus Megalopsalis (Neopilionidae: Enantiobuninae) is recognised as a senior synonym of the genera Spinicrus and Hypomegalopsalis, and seven new species are described in Megalopsalis: M. suffugiens, M. walpolensis, M. caeruleomontium, M. atrocidiana, M. coronata, M. puerilis and M. sublucens. A morphological phylogenetic analysis of the Enantiobuninae is also conducted including the new species. Monophyly of Neopilionidae and Enantiobuninae including ‘Monoscutidae’ is corroborated, with the Australasian taxa as a possible sister clade to the South American Thrasychirus.